Rivals when we work together: Team rivalry effects on performance in collaborative learning groups - Cătălina Oțoiu; Lucia Rațiu; Claudia Lenuța Rus (Administrative Sciences, 2019)
Team rivalry has been mostly studied in competition settings, between competing individuals or teams, and has been linked to positive performance outcomes due to its impact on increasing motivation. However, rivalry is not limited to such contexts, it can also occur in collaborative settings, among team members working on a collaborative task. We argue that in such settings rivalry in teams has a negative impact on team performance, due to its negative impact on team learning behaviors. We employed a time-lagged, survey-based design with a sample of 176 students (55 teams) to investigate the relationship between rivalry and team performance through team learning behaviors. Our results based on simple mediation analyses show that, for our sample, rivalry in teams was not in fact negatively correlated to learning behaviors. Furthermore, we did not find support for the hypothesized positive relationship between learning behaviors and team performance, nor for the partial mediation model we proposed. We show how a series of team and task characteristics could explain our results and discuss potential future directions in the study of rivalry in collaborative settings.
Keywords: 350; team rivalry; collaborative learning; team learning behaviors; team performance